2020
DOI: 10.3390/w12112957
|View full text |Cite
|
Sign up to set email alerts
|

Moving towards Effective First Nations’ Source Water Protection: Barriers, Opportunities, and a Framework

Abstract: It is well known that watershed-based source water protection programs are integral to the provision of clean drinking water. However, the involvement of Indigenous communities in these programs is very limited in Canada, which has contributed to the vulnerability of Indigenous source waters to contamination. Through a partnership with an Anishinaabe community, this research aimed to identify challenges and opportunities for communities and practitioners to improve the protection of Indigenous source waters in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 43 publications
0
11
0
Order By: Relevance
“…Another important element of forming relationships is listening. A practitioner interviewed for Marshall et al's [70] work to develop an effective source-water protection plan stated that the most important lesson they had learned was to listen. Similarly, Matson et al [78] list actively listening to Indigenous perspectives as one of their ten tenets for responsible research.…”
Section: "Long-term Personal Relationships and Trust" (Inspired By Re...mentioning
confidence: 99%
See 2 more Smart Citations
“…Another important element of forming relationships is listening. A practitioner interviewed for Marshall et al's [70] work to develop an effective source-water protection plan stated that the most important lesson they had learned was to listen. Similarly, Matson et al [78] list actively listening to Indigenous perspectives as one of their ten tenets for responsible research.…”
Section: "Long-term Personal Relationships and Trust" (Inspired By Re...mentioning
confidence: 99%
“…The scoping review also revealed examples where project teams collaborated to "indigenize" WKS frameworks or structures (e.g., source-water protection plans, environmental assessments), so they aligned with the values of the community [70,89,112,[156][157][158]. Wesche and Armitage [159] used qualitative scenarios (a WKS framework) to understand the vulnerability of an Indigenous community to climate change but ensured the scenarios were communicated through story and visual representations to reflect Indigenous ways of knowing.…”
Section: "There Is No Magic Recipe" (Inspired By Gérin-lajoie Et Al [...mentioning
confidence: 99%
See 1 more Smart Citation
“…27 Marginalized people typically lack clean safe drinking water, and this is a serious issue impacting the health and well-being of Indigenous communities around the world. [28][29][30][31][32] In Canada, First Nation Peoples face multiple water issues including boil water advisories. Boil Water Advisories (BWAs) are issued when water is known, or suspected to be, or could become unsafe for human consumption and range from do not consume to do not use the tap under any circumstance.…”
Section: Unhealthy Watermentioning
confidence: 99%
“…Source water protection is a complex process that must consider a number of sociopolitical and technical factors, including jurisdictional considerations, flow and transport of water and contaminants in the natural environment, and built infrastructure [1]. While many advances have been made towards protecting drinking water sources around the world in recent years [2][3][4][5][6][7], issues persist in many environments, including vulnerable hydrogeology, aging or inappropriate infrastructure, and where socio-economic and other factors have made it difficult to implement adequate source water protection measures, as is the case in many rural and Indigenous communities [3,5,6].…”
Section: Introductionmentioning
confidence: 99%